Concomitant THC and stress adolescent exposure induces impaired fear extinction and related neurobiological changes in adulthood. (January 2019) - Saravia, Rocio; Ten-Blanco, Marc; Julià-Hernández, Marina; Gagliano, Humberto; Andero, Raül; Armario, Antonio; Maldonado, Rafael; Berrendero, Fernando
Abstract: Δ 9 -tetrahydrocannabinol (THC) consumption during adolescence is reported to be a risk factor for the appearance of psychiatric disorders later in life. The interaction between genetic or environmental events and cannabinoid exposure in the adolescent period can also contribute to exacerbate behavioural deficits in adulthood. Here we investigate the effects of THC treatment as well as the consequences of concomitant THC and stress exposure during adolescence in the extinction of fear memory in adult mice. Adolescent mice treated with THC and exposed to stress exhibit impaired cued fear extinction in adulthood. However, no effect was observed in animals exposed to these two factors separately. Notably, resistance to fear extinction was associated with decreased neuronal activity in the basolateral amygdala (BLA) and the infralimbic prefrontal cortex, suggesting a long-term dysregulation of the fear circuit. These changes in neuronal activation were paralleled with structural plasticity alterations. Indeed, an increase of immature dendritic spines in pyramidal neurons of the BLA was revealed in mice simultaneously exposed to THC and stress. Corticosterone levels were also enhanced after the cued fear conditioning session in the same experimental group. These results show that an interaction between cannabis exposure and stress during adolescence may lead to long-term anxiety disorders characterized by the presence of pathological fear. Highlights: Concomitant THC and stress adolescent exposure impairs fear extinction in adulthood. Concomitant THC and stress adult exposure does not alter fear extinction. IL and BLA activity is reduced due to simultaneous THC/stress adolescent exposure. Concomitant THC/stress adolescent exposure alters BLA structural plasticity.